Pengembangan Model Pembelajaran Berbasis Proyek Untuk Pendidikan Vokasional Agribisnis - Edi Sulaiman; Ayu Dian Pratiwi Permatahati; Ainun Silvi Asya; , Sa’idy (Bulletin of Community Engagement, 2021)
This research aims to develop a Project-Based Learning (PjBL) model specifically designed for vocational agribusiness education to address the issue of conventional and less contextual learning approaches that hinder students' engagement and competence development. The study employed a Research and Development (R&D) method, adopting a modified Borg and Gall model consisting of seven stages: preliminary study, model planning, initial product development, limited trial, product revision, field testing, and final product refinement. The research was conducted at SMK Karya Bhakti Pringsewu, involving students of the agribusiness expertise program. Data were collected through observation, interviews, expert validation sheets, student learning outcome tests (pre-test and post-test), and perception questionnaires. The results indicate that the developed model is both feasible and effective. Expert validation showed that the model met content and design standards with a "good" category, The implementation of the model significantly improved student learning outcomes, increased active participation, and enhanced vocational competencies, particularly in entrepreneurial attitudes and real-world problem-solving. Furthermore, students and teachers gave positive responses regarding the practicality and meaningfulness of the learning experience. The study concludes that Project-Based Learning is a suitable and impactful model for improving the quality of vocational education in agribusiness.